IMPLEMENTASI PROGRAM EKSTRAKURIKULER DALAM MENUNJANG PRESTASI PESERTA DIDIK DI SD 1 DARUL HIKAM BANDUNG - Sinta Hardianti; Yulia Afida Damayanti; Nafila Fitrotul Laili; Fatimatuz Zahro'; Elya Umi Hanik (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aims to find out how the application of extracurricular activities in supporting the level of student achievement, because it not only refers to the theory of extracurricular activities but is also able to improve the achievements and skills of students at SD DarulHikam. The data collection of this research used a qualitative descriptive analysis approach and attended seminars. Sources of research data include oral and written, namely in the form of field study observations, seminars, documentation and written sources such as journals, theses and the official website of SD DarulHikam. The results of field study observations that have been carried out show that the implementation of extracurricular at SD DarulHikam is carried out every week or according to schedule, the end of the extracurricular implementation at SD DarulHikam is marked by holding extracurricular performances every 1 year or at the end of the school year. With extracurricular performances held by SD DarulHikam, students can appear confident in showing their interests and talents. Extracurricular activities have a very positive effect because they can provide motivation for academic and non-academic achievement. Based on the data that has been obtained, it can be seen that the implementation of the extracurricular program at SD 1 DarulHikam Bandung is very superior so that it can lead students to achieve academic and non-academic achievements. Keywords: Implementation; Program; Extracurricular; Performance.